2009
DOI: 10.1124/jpet.109.162297
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Toxicity and Metabolic Activation of Dauricine in CD-1 Mice

Abstract: Dauricine is the major bioactive component isolated from the roots of Menispermum dauricum D.C. and has shown promising pharmacological activities with a great potential for clinic use. However, the adverse effects and toxicity of the alkaloid are unfortunately ignored. The objective of the current study was to evaluate the toxicity of dauricine in vitro and in vivo. Mice (CD-1) were treated intraperitoneally with dauricine at various doses, and sera and lung lavage fluids were collected after 24 h of treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…The effects of CADPE in bone homeostasis are similar to the widely used osteoporosis drugs, bisphosphonates, which also inhibit bone digestion by osteoclasts and stimulate the formation of osteoblast precursors. (43) Therefore, further investigation will be needed to understand the mechanism of CADPE's involvement in osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CADPE in bone homeostasis are similar to the widely used osteoporosis drugs, bisphosphonates, which also inhibit bone digestion by osteoclasts and stimulate the formation of osteoblast precursors. (43) Therefore, further investigation will be needed to understand the mechanism of CADPE's involvement in osteoblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a derivative of dauricine ( N -desmethyldauricine/LP-4) to further verify the precise cellular machinery regulating the autophagic cell death. Derivatives of dauricine are of interest since dauricine has been shown in vitro to process anti-cancer property in colon (Yang et al, 2010), lung (Jin et al, 2010), breast (Tang et al, 2009), and urinary cancers (Wang et al, 2012). In fact, our previous findings point toward potential use of dauricine in multidrug- and apoptosis-resistant cancers intervention (Law et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we previously found that, dauricine induced autophagic cell death with a higher IC 50 value (Law et al, 2014) toward the cell lines MCF-7 (28.7 μM) and A549 (40.4 μM), while the IC 50 value corresponding to these cell lines upon LP-4 treatment are 1.8 to 2-fold lower as demonstrated in this report: MCF-7 (15.5 μM) and A549 (19.7 μM). Such higher cytotoxicity could be a result of the existence of the electrophilic quinone methide group on LP-4 (Wang et al, 2009; Jin et al, 2010). However, the molecular mechanisms for inducing the higher cellular toxicity as demonstrated might be attributed to increased autophagic effect (unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that para-methylene phenol moiety in dauricine underwent CYP3A4-mediated bioactivation to generate a quinone methide reactive intermediate, which was trapped with nucleophilic agents such as reduced glutathione [73]. The reactive quinone methide intermediate plays a dominant role in pulmonary toxicity induced by dauricine in CD-1 mice [74].…”
Section: Herbal Components Containing Alkenesmentioning
confidence: 99%